IMPLEMENTATION OF SHARIA COMPLIANCE IN INNOVATIVE PRODUCT DEVELOPMENT IN SHARIA BANKS - Ratnasari, Aireni; Mukhlas, Oyo Sunaryo; Rusyana, Ayi Yunus; Noor Silmi Sudrajat, Ajeung Syilva Syara; Jamaludin , Jujun (DE'RECHTSSTAAT, 2024)
The establishment of sharia financial institutions is a response to the need for Muslims to carry out aspects of their economic life in accordance with the principles of the Qur'an and Hadith, as well as to meet the need for interest-free banking. However, the main challenge for Islamic banks is to develop amidst the dominance of established conventional banking. The success of Islamic banks not only depends on the formal adoption of Islamic rules in muamalat, but also on the consistency and trust of society in their compliance with sharia principles. This research aims to analyze the implementation of sharia compliance in the development of innovative products in sharia banks. This research uses a normative legal approach. by collecting data from legal literature and related documents, as well as analyzing sharia bank policies and practices in developing innovative products. The research results show that Islamic banks that are successful in developing innovative products are those that are able to maintain consistency with sharia principles in every stage of the product, from planning to implementation. The main obstacles include challenges in implementing a fair and transparent profit sharing system, as well as the need for skilled human resources in sharia bank operations. Nevertheless, there is significant potential for Islamic banks to expand financial access for low-income communities through products that comply with sharia principles.